Effects of Unical Feed on Fecundity and Gonad Development of Clarias gariepinus; A Comparative Study with Coppens Commercial Feed in Earthen Pond - Ekanem, Albert Philip; Eyo, Victor Oscar; James Philip Udoh; Udo, Nsisong Emmanuel (International Journal of Science and Research, 2013)
This study was carried out to determine and compare the fecundity and gonad development of Clarias gariepinus fed Unical and Coppens feeds in earthen pond for 150 days in the University of Calabar fish farm. Twenty (20) fingerlings of C. gariepinus with mean bulk weight of 0.20 ± 0.02 kg were stocked in four hapas A1, A2, B1 and B2 fixed in experimental earthen pond measuring 1.5 x 1.0 x 1.0m3 . Fish in hapas A1 and A2 were fed Unical feed while fish in hapas B1 and B2 were fed Coppens feed. The design was duplicated three times for the purposes of comparisons. The fishes were fed twice daily at 5% of their body weight. Mean fecundity was 14388.89 ± 4180.89 eggs for fish fed Unical feed and 15575.0 ± 4333.97 eggs for fish fed Coppens feed respectively with no significant difference (P>0.05) between the two feeds. Mean egg diameter (1.44 ± 0.07mm) for Unical feed was not significantly different (P>0.05) from that of Coppens (1.44 ± 0.05mm). Mean gonadosomatic index of fish fed Unical feed (1.60 ± 0.78%) was not significantly different (P>0.05) from fish fed Coppens feed (1.85 ± 0.50%). There was a lineal relationship between fecundity and gonadosomatic index with fish weight, total length and gonad weight of C. gariepinus fed the two feeds. Physicochemical parameters (pH, temperature, dissolved oxygen and ammonia) of water were within acceptable range for tropical fish culture. Unical aqua feed is recommended for C. gariepinus culture on the basis of cost effectiveness as compared to Coppens commercial feed.
Keywords: Unical feed; Coppens feed; Fecundity and Gonad development; Clarias gariepinus